Mesoscopic simulation of alkylimidazoline self-aggregation in aqueous solution. Issue 7 (3rd July 2017) - Kong, Xiangjun; Qian, Chengduo; Zhao, Pinhui; Lin, Yan; Fan, Weiyu
ABSTRACT: A dissipative particle-dynamics method was used to simulate the self-aggregation behavior of 15 alkylimidazoline surfactants of different structures. The effects of concentration and structure of hydrophilic and lipophilic groups of the alkylimidazolines on the configuration and aggregation number ( N agg ) of the micelles were also explored. Results show that the concentration of the alkylimidazoline has a significant influence on the configuration of the micelles generated. More specifically, alkylimidazolines of different concentrations are found to generate different structures (spherical, rod-shaped, layered, and interlaced) in aqueous solution. At low (1–10 wt%) and medium (40 wt%) concentrations, the micelles generated in aqueous solution are spherical and rod-shaped, respectively. At higher concentrations (80 wt%), the micelles generated present interlaced shapes with rod-shaped and layered micelles when the length of the lipophilic chain is greater than C13 or the hydrophilic group is Hc . N agg is strongly dependent on alkylimidazoline concentration and increases as concentration increases. N agg is also greatly dependent on the structure of the hydrophilic and lipophilic groups present: it increases as the chain length of the lipophilic group increases but decreases as that of the hydrophilic group increases. GRAPHICAL ABSTRACT: